Menyingkap Kerumitan: Kajian Hukum Tentang Pemasangan Alat Peraga Kampanye Pemilu 2024 Pada Pohon - Phireri Phireri; Muh. Akbar Fhad Syahril; Nurul Annisa (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
Elections have been considered a measure of democracy because people can participate in determining their attitudes towards their government and country. Elections are important in the life of a state. Elections are part of a democratic system through which the people determine their representatives. In general elections, political campaigns are one way for candidates to introduce themselves and their programs to the public. However, in the implementation of political campaigns, some rules must be followed by the candidates so that the campaign runs in an orderly manner and does not violate the law. In the implementation of political campaigns, some rules must be followed by candidates so that the campaign runs in an orderly manner and does not violate the law. One of the things that is so synonymous with the campaign period is the increasingly crowded and large number of campaign props used by candidates/election participants and their success teams. This is one of the methods for candidates to conduct campaigns so that the public can know their entire vision, mission, program, and identity.